A Thermal Load Forecasting Algorithm Based on Trajectory Tracking. (17th November 2020) - Ling, Guo; Weiwei, Du; Jiancheng, Yang; Liping, Wang; Ping, Wan; Ling, Liu
Abstract : The heating load forecast provides a basis for saving heating energy. Considering the nonstationary, nonlinear, and large time-delay characteristics of thermal load, this paper introduces the trajectory tracking stability theory into the field of load forecasting and proposes a heuristic correction that can ensure the convergence of forecast errors and does not depend on the system prediction model algorithm. The Lyapunov method is used to derive an error convergence criterion that has nothing to do with the prediction model, and a heuristic correction algorithm is designed for the predicted value with error divergence trend to ensure the error convergence of the load forecast sequence.